Interpreting the projected frontal area in front crawl: determining the projected frontal area of each body segment - Washino, S.; Murai, A.; Kadi, T.; Narita, K.; Mankyu, H.; Yoshitake, Y. (Medicine & Science in Sports & Exercise, 2025)
Purpose This study aimed to provide evidence for the interpretation of the projected frontal area (PFA) during front crawl. To achieve this goal, we developed a method for calculating the PFA of each body segment using digital human technology and compared the pressure drag under two calculation conditions: a combination of the PFA with and without accounting for the horizontal velocity of each body segment.